Institutional Ownership and Financial Distress: The Moderating Effect of Executives with Foreign Experience - Kushermanto, Andi; Nurfadilah, Nurfadilah; Alisa, Inayah Risqi; Mahirun, Mahirun (Journal of Accounting Research, Organization and Economics, 2024)
Objective This research aims to analyze the influence of institutional ownership on financial distress and the role of executives with foreign experience as a moderating variable.Design/Methodology The object of this research is the consumer cyclical sector companies listed on the Indonesian Stock Exchange during the 20172021 period. The data sample was gained through purposive sampling and obtained from 47 companies that met the criteria. Partial Least Squares Structural Equation Modeling (PLS-SEM) using WarpPLS 8 is the analytical technique used in this research.Results This study provides evidence that institutional ownership can prevent or reduce financial distress as it functions to monitor company performance. The variable of executives with foreign experience strengthens the influence of institutional ownership on financial distress, which shows the role of executives with foreign experience in reducing the possibility of financial distress.Research limitations/implications This study was conducted in the consumer cyclical sector for five years of observation, which can limit the generalizability of its findings. The implications of this study are practical suggestions for the company's management to avoid financial distress and achieve long-term goals through the role of CEO in relation to its overseas background.Novelty/Originality In Indonesia, prior research has explored the impact of good corporate governance and the CEO's role in maintaining financial distress conditions. Nevertheless, none has investigated the overseas background aspect, namely the CEO with foreign experience, as one of the moderating factors that influence the GCG aspect of reducing financial distress, which is the originality of this study.